Use of Intravenous Pulse Steroids to Treat Allergic Bronchopulmonary Aspergillosis in a Non-Compliant Asthmatic Adolescent - Sara G. Hamad; Mutasim Abu-Hasan; Atqah AbdulWahab (MDPI AG, 2022)
Allergic bronchopulmonary aspergillosis (ABPA) is an immune-mediated inflammatory airway disease that predominantly affects patients with cystic fibrosis (CF) and, less commonly, patients with asthma. ABPA can lead to irreversible lung injury and bronchiectasis if not treated early and aggressively. Long-term oral steroids are the standard therapy of ABPA. However, it is associated with an increased risk of steroids side effects and possible medication noncompliance. Monthly intravenous pulse methylprednisolone (IV-PS) has been used as an alternative to oral steroids to treat CF-related ABPA with a reportedly similar clinical response and less steroid-related side effects. To our knowledge, the use of IV-PS in asthma-related ABPA has not been previously reported. We report the successful management of asthma-related ABPA in an adolescent using intravenous pulse methylprednisolone in addition to oral itraconazole with no significant steroid-related side effects.